Epidemiological, demographic, social, clinical features of manifestations of system red lupus in patients in Kazakhstan - B. G. Issayeva; E. A. Aseeva; M. M. Saparbayeva; S. M. Issayeva; M. M. Kulshymanova; S. M. Kaiyrgali; M. P. Bizhanova; K. Zh. Nurgaliyev; N. S. Akhtaeva; B. A. Kulymbetova; K. K. Rysbekova; S. K. Solovyev (Научно-практическая ревматология, 2021)
Objective: to study and analyze the dynamics of prevalence, demographic, social, and clinical manifestations of systemic lupus erythematosus (SLE) in patients living in Kazakhstan.Materials and methods. Official materials of the Ministry of Health of the Republic of Kazakhstan (2009–2018): statistical compendiums, a consolidated reporting form for medical treatment (N 12). 102 patients (100 women and 2 men) were included in the register of SLE with reliable SLE according to SLICC (ACR, 2012). Assessment of the debut of the disease was carried out according to archival material (medical history, outpatient records) of patients. The activity of the process was evaluated according to SLEDAI-2K, organ damage according to SLICC/ACR (2000).Results. The total number of patients with SLE over 10 years (2009–2018) more than doubled, the growth rate was 101%. The overwhelming majority of patients with SLE are women (91%). In the study group, Asians (83.33%) predominated by race, of which Kazakhs (76.47%) were young (mean age – 33.85±10.58 years), with a disease duration of 5 (2; 9) years, time from the appearance of the first signs to verification of SLE – 4.5 (3; 12) years. The prevailing acute (49.0%), subacute (33.3%), rather than chronic (18.7%) variants of the course, with high activity according to SLEDAI-2K – 17.64±8.80. The most common clinical manifestations of the disease: skin lesions (98%), joints (79.4%), nervous system (49%), hematological (54.9%) and immunological (100%) disorders. The absence of organ damage (0 points) was detected in 10 (9.8%) cases, low (1 point) – in 21 (20.6%), medium (2–4) – in 61 (59.8%), high (over 4) – in 10 (9.8%) patients.Conclusion. SLE remains a socially significant disease in Kazakhstan, as evidenced by the dynamics of the increase in incidence (101%) over 10 years (2009–2018). The prevalence of SLE is 24.7 per 100 thousand of the country’s population, lower than in other countries with a predominant Asian population or in comparison with Asian populations. A cohort of patients with SLE was represented by people of the Asian race (83.33%), Kazakhs (76.47%), and young people (33.85±10.58). The analysis revealed a delayed verification of the diagnosis of SLE (on average 4.5 (3; 12) years). Acute variants of the course of the disease with high disease activity according to SLEDAI-2K prevail. Common clinical manifestations of SLE are skin lesions, both acute and chronic (98%), joints (79.4%), damage to the nervous system (49%), hematological (54.9%) and immunological disorders (100%).